2006
DOI: 10.1002/jhet.5570430514
|View full text |Cite
|
Sign up to set email alerts
|

Paal knorr reaction for novel pyrrolo[2,3-d]pyrimidines

Abstract: An expeditious and convenient solid supported synthesis of 1,3,7‐triaryl‐6‐phenyl‐2‐thioxo‐1,2,3,7‐tetrahydropyrrolo [2,3‐d]pyrimidin‐4‐one derivatives from readily accessible N,N‐disubstituted thiobarbituric acids under microwaves utilising Paal Knorr reaction is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This method consists of reaction of γ-diketone and primary amines. From acidic catalysts that used for the synthesis of N-substituted pyrroles can be mentioned to the zeolite, [27] Ti (O-i-Pr) 4, [28] p-TSA, [29] Al 2 O 3, [30] SnCl 2 .2H 2 O, [31] Sc (OTf) 3, [32] RuCl 3, [33] InCl 3, [34] layered zirconium phosphate and sulfophenyl phosphonate. [35] There are some reported procedures for the synthesis of polysubstituted pyrroles in the presence of FeCl 3, [36] AgOAc, [37] TiCl 4 /Zn, [38] I 2 /ZnCl 2, [39] and Sm (O i Pr) 3 [40] catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This method consists of reaction of γ-diketone and primary amines. From acidic catalysts that used for the synthesis of N-substituted pyrroles can be mentioned to the zeolite, [27] Ti (O-i-Pr) 4, [28] p-TSA, [29] Al 2 O 3, [30] SnCl 2 .2H 2 O, [31] Sc (OTf) 3, [32] RuCl 3, [33] InCl 3, [34] layered zirconium phosphate and sulfophenyl phosphonate. [35] There are some reported procedures for the synthesis of polysubstituted pyrroles in the presence of FeCl 3, [36] AgOAc, [37] TiCl 4 /Zn, [38] I 2 /ZnCl 2, [39] and Sm (O i Pr) 3 [40] catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Various literature reported that, both synthetic as well as natural nitrogen containing heterocyclic molecules possesses a significant pharmaceutical importance, a large number have been made up to clinics for health care worldwide. Pyrazole and pyrazolone are classes of heterocycles which exhibits diverse chemical and biological properties [2][3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%